Financial Evaluation and Social Impact of Community-Based Health Projects: A Case Study of the XYZ Indonesia Foundation - Rahmat Saleh (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
This study assesses the financial feasibility and social impact of a community-based health initiative by the XYZ Indonesia Foundation, which provides free HIV testing to key populations. Using evaluative analysis and descriptive quantitative methods, the research applies financial indicators such as Payback Period (PP), Accounting Rate of Return (ARR), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI). Results show a PP of 4.28 years, an ARR of 14.01 percent, a negative NPV of Rp 246,530,081, an IRR of 7.26 percent, and a PI of 0.885, indicating the project is not financially viable. Despite this, the initiative delivers significant social benefits, including improved access to health services for vulnerable groups, reduced HIV-related stigma, and greater community engagement. Although the project does not achieve commercial viability, its social value supports continued investment through social funding, public-private partnerships, and enhanced program governance.